2013
DOI: 10.1017/s1368980013001997
|View full text |Cite
|
Sign up to set email alerts
|

Fast-food consumers in Singapore: demographic profile, diet quality and weight status

Abstract: Objective: To determine the demographic profile of fast-food consumers among adult Singapore residents and ascertain whether fast-food consumption frequency is associated with diet quality and weight status. Design: A nationally representative cross-sectional survey including an FFQ and anthropometric measures. Participants were grouped based on their fast-food consumption frequency as non-consumer, occasional consumer or regular consumer, with regular defined as at least once per week. Setting: Individuals li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 32 publications
6
35
0
1
Order By: Relevance
“…Despite fast food chains being easily accessible in Singapore, an examination of the frequency of fast food consumption shows a counter-intuitive pattern. In a population-based survey, 37% were nonconsumers, 43% were occasional consumers (less than once a week but more than once a month) and 20% consumed fast foods at least once a week [4]. A similar low frequency of western-styled fast food consumption was also reported in Malaysia, Indonesia, and the Philippines [5].…”
Section: Introductionmentioning
confidence: 70%
“…Despite fast food chains being easily accessible in Singapore, an examination of the frequency of fast food consumption shows a counter-intuitive pattern. In a population-based survey, 37% were nonconsumers, 43% were occasional consumers (less than once a week but more than once a month) and 20% consumed fast foods at least once a week [4]. A similar low frequency of western-styled fast food consumption was also reported in Malaysia, Indonesia, and the Philippines [5].…”
Section: Introductionmentioning
confidence: 70%
“… Duffey et al, 2007 ( 14 ) Two-year follow-up of adults participants in Mediterranean cohort study, n= 7194 More consumption of hamburger, pizza, and sausages increased risk of weight gain (≥3 kg during a 5 past year) (OR=1.2, 95% CI=1-1.4) Bes-Rastrollo et al, 2006 ( 15 ) Cross-sectional study of school children, n=1033 Higher consumption of fast food was associated with higher BMI Z score (β=0.08, 95% CI=0.03-0.14), higher body fat (β=2.06, 95% CI=1.33-2.79) and an increased risk of obesity (OR=1.23, 95% CI=1.02-1.49). Jeffery et al, 2006 ( 17 ) Cross-sectional study of Singaporean adults, n=1627 The risk of abdominal obesity was 1.24 (95% CI=1.03- 1.51) and 1.52 (95 % CI= 1.32- 1.77) in regular consumers and occasional consumers of fast foods. Whitton et al, 2013 ( 19 ) A cross-sectional study of adults participated in Michigan Behavioral Risk Factor Survey Increased risk (OR=1.81, 95% CI=1.35-2.44) of obesity was observed in adults with consuming ≥3 times/week compared to <1 time/week fast foods.…”
Section: Resultsmentioning
confidence: 99%
“…Findings on diet quality and weight status from other research have been mixed. Several cross-sectional studies have found a relationship between higher BMI and lower diet quality scores [48,49,50] and lower risk of abdominal obesity with lower diet quality [51]. Conversely, other research has found that adults with a higher BMI had better diet quality [35], and it was postulated that this might be due to misreporting, as overweight and obese participants are more likely to misreport foods than others [35].…”
Section: Discussionmentioning
confidence: 99%